2019
DOI: 10.1038/s41587-019-0363-0
|View full text |Cite
|
Sign up to set email alerts
|

The industrial yeast Pichia pastoris is converted from a heterotroph into an autotroph capable of growth on CO2

Abstract: The methylotrophic yeast Pichia pastoris is widely used in the manufacture of industrial enzymes and pharmaceuticals. Like most biotechnological production hosts, P. pastoris is heterotrophic and grows on organic feedstocks that have competing uses in the production of food and animal feed. In a step toward more sustainable industrial processes, we describe the conversion of P. pastoris into an autotroph that grows on CO 2 . By addition of eight heterologous genes and deletion of three Users may view, print, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
196
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 238 publications
(199 citation statements)
references
References 53 publications
1
196
0
2
Order By: Relevance
“…Many reasons may lead to this problem, but inefficiency intermediates supplement may be an important reason. Therefore, Clarify intermediates recycle regulation mechanism in methanol utilization pathway maybe not only beneficial for other non-native methylotrophic microbes construction but also would promote other one-carbon source utilization [4,26]. In Saccharomyces cerevisiae, Tkl1 has been shown as the rate-limiting factor in NOP pathway [27].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many reasons may lead to this problem, but inefficiency intermediates supplement may be an important reason. Therefore, Clarify intermediates recycle regulation mechanism in methanol utilization pathway maybe not only beneficial for other non-native methylotrophic microbes construction but also would promote other one-carbon source utilization [4,26]. In Saccharomyces cerevisiae, Tkl1 has been shown as the rate-limiting factor in NOP pathway [27].…”
Section: Discussionmentioning
confidence: 99%
“…As an important heterologous protein expression system, more than 1,000 proteins have been successfully expressed via P. pastoris, including angiostatin, a-glucosidase [1]and Anti-CEACAM5 nanobody [2,3]. Moreover, as the rare methylotrophic microbes, detailed methanol metabolic pathway especially important intermediates recycle pathway not only significantly promotes other 3 methylotrophic microbes construction but also promotes autotrophic microorganism design [4]. Many results showed that the robust alcohol oxidase 1 promoter (P AOX1 ) contributes most to this successful expression system [5].…”
Section: Introductionmentioning
confidence: 99%
“…Engineered compartmentalization has garnered considerable attention in recent years 7,[14][15][16][17][18] .…”
Section: Introductionmentioning
confidence: 99%
“…Organelles have also been harnessed for the reactions that they natively perform. For example, the endoplasmic reticulum and Golgi in Chinese Hamster Ovary cells are used for the glycosylation of heterologous proteins 26 , and recently the methanol assimilation pathway in the peroxisomes of Pichia pastoris was engineered into a carbon dioxide fixation pathway where six native peroxisome enzymes were utilized 17 . Advances in the development of synthetic compartments have also been reported, including the synthesis of prokaryotic encapsulin nanocompartments in eukaryotes 15,27 , bacterially-derived proteinaceous gas vesicles in mammalian cells 28 , and light-inducible phase-separated organelles in yeast 16 .…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have made considerable progress in establishing carbon fixation pathways in heterotrophic organisms, with the longterm goal of achieving synthetic autotrophy, which could pave the way towards sustainable bioproduction schemes rooted in CO2 and renewable energy 4,5 . Most notably, overexpression of phosphoribulokinase and Rubisco, followed by long-term evolution, enabled the industrial hosts Escherichia coli 6,7 and Pichia pastoris 8 to synthesize all biomass from CO2 via the RuBP cycle. Also, overexpression of enzymes of the 3hydroxypropionate bicycle established the activity of different modules of this carbon fixation pathway in E. coli 9 .…”
Section: Introductionmentioning
confidence: 99%